Increased incidence of seronegative autoimmune hepatitis in children during SARS-CoV-2 pandemia period - Schmutz, Muriel; Chartier, Suzanne; Leblanc, Thierry; Mussini, Charlotte; Gardin, Antoine; Gonzales, Emmanuel; Roque-Afonso, Anne-Marie; Le Cam, Solene; Hery, Geraldine; Neven, Benedicte; Charbel, Ramy; Vartanian, Jean-Pierre; et al. (Frontiers in Immunology, 2024)
Background: Seronegative autoimmune hepatitis in children is a rare but potentially severe disease, sometimes requiring liver transplantation. This type of hepatitis may be associated with various immunological and hematological disorders, ranging from isolated lymphopenia to aplastic anemia. Precise pathophysiological mechanisms are still unknown, but the role viruses cannot be excluded, either as directly pathogenic or as triggers, responsible for an inappropriate immune stimulation. Having the impression of an increasing number of seronegative autoimmune hepatitis since the beginning of SARS-CoV-2 pandemia period, we hypothesized that SARS-CoV-2 virus could be an infectious trigger. Methods: We conducted a retrospective, observational, descriptive study about children with seronegative autoimmune hepatitis, in a tertiary care center, between 2010 and 2022.Results: Thirty-two patients were included. The overall incidence of seronegative autoimmune hepatitis increased 3.3-fold in 2020-2022, during the SARS-CoV-2 pandemia period (16 patients in 2.8 years) compared with 2010-2019 the pre pandemia period (16 patients in 9 years). Patients' clinical and biochemical liver characteristics did not differ between the two periods. Hematological damages were less severe during the pandemia period. Immunological studies revealed a dysregulated immune response. The initiation of immunosuppressive therapy (corticosteroids ± cyclosporine) was earlier during the pandemia period than before.In cases of undetermined acute hepatitis, an immune-mediated origin should be considered, prompting a liver biopsy. If the histological aspect points to an immune origin, immunosuppressive treatment should be instituted even though autoimmune hepatitis antibodies are negative. Close hematological monitoring must be performed in all cases. The 3.3-fold increase of cases during the SARS-CoV-2 pandemia will need to be further analyzed to better understand the underlying immunological mechanisms, and to prove its potential involvement.